(untitled) (Politeja, 2020)
Good Practices to Disseminate Knowledge about Coordination of Pension Systems in Selected European Union Countries. Recommendations for Poland More and more Poles are using EU regulations coordinating pension systems. These are both people who currently live in another EU country as well as people who return to Poland after working abroad. The method of analysing the literature on the subject was used and the studies on the knowledge, opinions and attitudes of Poles regarding social insurance in Poland and the coordination of pension benefits were reviewed. An analysis of current national surveys indicates that the level of this knowledge is very low. Knowledge about EU legislation functions at the expert and scientific level. The use of European experience regarding the dissemination of knowledge on the coordination of pensions seems to be necessary; therefore, selected initiatives of popularization of the knowledge in selected EU Member States were presented, thus creating recommendations for Poland.